Implementation of Data Generator for Process Mining Applications - Yuzkat, Mecit; Sen, Bugra; Caymaz, Hasan Kaan; Karabiber, Fethullah (IEEE, 2015)
Process Mining is a new research area that tries to answer the business world needs such as improvement of productivity and efficiency. The aim of process mining is to discover, monitor and improve business processes. Starting point of process mining is event logs which contain information about every step of a business process. With the help of Process Mining techniques, we can analyze the event logs to discover, monitor and improve business processes. The aim of this study is to develop a simulator which generates data that will lead to the development and analysis of business processes. A web system has been created under this study that would work with various business process models and bring out significant data from such models. More productive and efficient processes may be developed using the system. The system consists of three modules. The first module allows the users create a process model. In this module, the users can create their own business model using the interface or can choose among the other models already designed. In the second module, the simulation of the team based data can be performed using the process models already created. In the third module, which is named as analysis, some meaningful information such as the time, source and cost can be extracted using generated data. Consequently, the process can be improved by examining the extracted information.
Keywords: Process Mining; Data Analysis; Simalation; Data Generator; Performance Analysis; Engineering; Telecommunications